Sistem Penunjang Keputusan Pemilihan Paket IndiHome Calon Pelanggan Menggunakan Metode Weighted Product - Nadafi'ah Hari Fitri; Agus Sidiq Purnomo (INFORMAL: Informatics Journal, 2020)
PT Telekomunikasi Indonesia is one of big companies in Indonesia that focuses on technology field. PT Telekomunikasi Indonesia has an important role in providing internet access, of which product is IndiHome. There are several types of internet package to provide the internet access offered by PT Telekomunikasi Indonesia. In this research, the writer aims to help prospective customers make the best decision. Thus, the writer divides the prototype of Decision Support System for Choosing IndiHome Package for Prospective Customers Using WP Method in 4 (four) variables, namely speed, price, internet quota, and need. Based on the results of the test conducted with 48 data using both manual and system calculation, there are 42 compatible data with a percentage of 87,5%.